Preparation method of heat dissipation aerogel for lithium battery
By crosslinking cellulose and introducing nanocopper particles, a high-thermal conductivity and high-strength heat dissipation aerogel was prepared, which solved the problem of insufficient thermal conductivity and mechanical strength of traditional cellulose aerogels in lithium batteries, and achieved better heat dissipation and stress absorption effects.
Patent Information
- Application Number
- CN202411919443.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
Traditional cellulose aerogels have poor thermal conductivity and heat dissipation performance in lithium batteries and have poor mechanical strength, which limits their practical application.
By reacting with 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, and introducing copper salts to generate and disperse nanocopper particles. Combined with a freeze-drying process, a high thermal conductivity and high strength heat dissipation aerogel was prepared.
It significantly improves the thermal conductivity and mechanical properties of the aerogel, allowing it to dissipate heat and absorb stress more effectively, and is suitable for components such as lithium battery shells.
Smart Images

Figure BDA0005207587900000031 
Figure BDA0005207587900000081 
Figure BDA0005207587900000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogels, and in particular relates to a method for preparing heat dissipation aerogel for lithium batteries. Background Art
[0002] Cellulose is the most abundant polysaccharide polymer compound in the world. It is cheap, easy to obtain, green and pollution-free. The development and utilization of cellulose is a research trend. Cellulose can be processed by chemical cross-linking, freeze-drying and other processes to obtain aerogel materials, which are widely used in adsorption materials, phase change materials, thermal insulation materials and other fields. Cellulose aerogel can be made into carbon aerogel for lithium battery electrodes, aerogel membrane for battery separators and other materials, and has broad development prospects in lithium batteries. However, due to the low thermal conductivity of traditional cellulose aerogel, its thermal conductivity and heat dissipation performance are poor, and its mechanical strength is poor, so its practical application is greatly limited.
[0003] Lithium batteries have the advantages of high energy density, excellent cycle performance, no memory effect, and green environmental protection. And with the development of science and technology, lithium batteries have become the mainstream batteries for new energy vehicles and electronic devices. However, during actual use, lithium batteries generate more heat, and the thermal conductivity and heat dissipation performance of components such as lithium battery shells are poor, which seriously affects the performance of lithium batteries. The present invention aims to prepare a heat-dissipating aerogel material with high thermal conductivity and high strength, and expand the practical application of cellulose aerogel in components such as lithium battery shells. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a heat dissipation aerogel with high thermal conductivity and high strength for use with lithium batteries.
[0005] The technical solution provided by the present invention is: a method for preparing heat dissipation aerogel is:
[0006] (1) Add N,N-dimethylformamide and dialdehyde cellulose to a reaction vessel, stir and mix, then add 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene (structural formula: ), after stirring the reaction, the reaction vessel is placed in an ice water bath to precipitate the precipitate, which is filtered, washed with ethanol, and dried to cross-link the carboxylated cellulose.
[0007] (2) Add copper salt to deionized water, stir to dissolve, then add cross-linked carboxylated cellulose, disperse by ultrasonication in an ultrasonicator, and then stir and adsorb at 20-40°C for 6-18 hours, then add sodium borohydride and water, stir at 20-30°C for reduction reaction for 24-36 hours, filter, wash with deionized water, then add to deionized water, disperse by ultrasonication, and finally pre-freeze at -25°C to -35°C for 6-10 hours, and then freeze-dry in a freeze dryer at -50°C to -60°C for 36-48 hours to obtain heat dissipation aerogel.
[0008] Further, the mass of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene is 50-180% of the mass of dialdehyde cellulose.
[0009] Furthermore, the reaction in (1) is carried out at 45-60°C for 18-36 hours.
[0010] Furthermore, the mass of the copper salt is 80-300% of the mass of the cross-linked carboxylated cellulose.
[0011] Furthermore, the copper salt is copper chloride, copper sulfate or copper nitrate.
[0012] Further, the preparation method of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene is as follows: N,N-dimethylformamide, 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene in a ratio of 1 mol:(3-3.3) mol:(0.08-0.1) mol:(9-10.8) mol, 3-amino-5-bromobenzoic acid, palladium acetate, sodium carbonate are added to a reaction vessel provided with a condenser reflux tube, and deionized water is added, nitrogen is introduced, heated to 85-100°C, stirred for reaction for 5-10h, deionized water is added, the reaction vessel is placed in an ice water bath to precipitate the precipitate, filtered, washed with deionized water, and then recrystallized with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene. The reaction formula is:
[0013]
[0014] Further, the application of heat dissipation aerogel in lithium batteries.
[0015] The technical effect of the present invention is as follows: the present invention utilizes 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene containing multiple amino groups to undergo a Schiff base condensation reaction with the aldehyde group of dialdehyde cellulose to achieve cross-linking of the dialdehyde cellulose to obtain cross-linked carboxylated cellulose containing carboxyl groups, and then the introduced carboxyl groups react with copper salts such as copper chloride to form copper ions. 2+ It has a strong coordination chelation effect and can 2+ Uniformly adsorbed into the skeleton and pores of cross-linked cellulose, and then reduced by sodium borohydride, Cu2+ Nano copper particles are generated and evenly distributed in the skeleton of cross-linked cellulose. Finally, they are freeze-dried to obtain heat dissipation aerogel. Nano copper particles are well dispersed in aerogel and are not easy to agglomerate. They form heat conduction paths in aerogel, significantly improving the thermal conductivity of aerogel and showing better thermal conductivity and heat dissipation performance. They can be applied to components such as the outer shell of lithium batteries to achieve heat dissipation effects.
[0016] After the dialdehyde cellulose of the present invention is cross-linked with 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, a rigid terphenylbenzene structure is introduced into the skeleton of the aerogel, which significantly improves the strength and modulus of the cellulose aerogel. At the same time, the nano copper particles themselves have high mechanical strength and are embedded in the aerogel matrix to support the skeleton, so that the aerogel exhibits higher compression stress, compression modulus and mechanical properties. It can be applied to components such as the outer shell of a lithium battery to absorb and buffer stress, and can be used as a protective layer to protect lithium battery components. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] The CAS number of the 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene of the present invention is 900795-73-5.
[0019] The CAS number of 3-amino-5-bromobenzoic acid is 42237-85-4.
[0020] The CAS number of 1,3,5-tri(4-aminophenyl)benzene is 118727-34-7.
[0021] Microcrystalline cellulose brand: Yuanye S14009.
[0022] Preparation of dialdehyde cellulose: 10g of microcrystalline cellulose is placed in a sodium hydroxide solution with a mass fraction of 15%, soaked for 24h, filtered, washed with deionized water, and dried to obtain alkali-treated microcrystalline cellulose. 300mL of deionized water and 12g of sodium periodate are added to the reaction bottle, sulfuric acid is added dropwise to adjust the pH to 2, 10g of microcrystalline cellulose is added, stirred and mixed, stirred and reacted at 35°C for 2h, 800mL of ethylene glycol is added to remove unreacted sodium periodate, filtered, washed with deionized water, and dried to obtain dialdehyde cellulose.
[0023] Example 1
[0024] (1) Add 800 mL of N,N-dimethylformamide and 50 mmol of 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene into a reaction vessel equipped with a condenser reflux tube. ), 165 mmol 3-amino-5-bromobenzoic acid, 5 mmol palladium acetate, 450 mmol sodium carbonate, and add 100 mL of deionized water, introduce nitrogen, heat to 100 ° C, stir and react for 5 hours, add deionized water, place the reaction container in an ice water bath to precipitate the precipitate, filter it, wash it with deionized water, and then recrystallize it with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene.
[0025] (2) Add 500 mL of N,N-dimethylformamide and 20 g of dialdehyde cellulose to a reaction container, stir and mix, then add 20 g of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, stir and react at 45° C. for 36 hours, place the reaction container in an ice water bath, precipitate, filter, wash with ethanol, and dry to cross-link the carboxylated cellulose.
[0026] (3) Add 2.4 g of copper chloride to 100 mL of deionized water and stir to dissolve. Then add 3 g of cross-linked carboxylated cellulose and disperse it by ultrasonication in an ultrasonicator. Then stir and adsorb it at 20°C for 18 h. Then add 52 g of sodium borohydride and 300 mL of water and stir to perform reduction reaction at 25°C for 24 h. Filter and wash with deionized water. Then add it to 200 mL of deionized water and disperse it by ultrasonication. Finally, pre-freeze it at -25°C for 10 h. Then freeze-dry it at -50°C in a freeze dryer for 48 h to obtain heat dissipation aerogel.
[0027] Example 2
[0028] (1) Add 600 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene, 150 mmol of 3-amino-5-bromobenzoic acid, 4.4 mmol of palladium acetate, 540 mmol of sodium carbonate, and 120 mL of deionized water to a reaction vessel equipped with a condenser reflux tube, introduce nitrogen, heat to 85° C., stir to react for 10 h, add deionized water, place the reaction vessel in an ice water bath to precipitate, filter, wash with deionized water, and then recrystallize with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene.
[0029] (2) Add 500 mL of N,N-dimethylformamide and 20 g of dialdehyde cellulose to a reaction container, stir and mix, then add 25 g of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, stir and react at 50° C. for 24 h, place the reaction container in an ice water bath, precipitate, filter, wash with ethanol, and dry to cross-link the carboxylated cellulose.
[0030] (3) Add 4.5 g of copper sulfate to 100 mL of deionized water and stir to dissolve. Then add 3 g of cross-linked carboxylated cellulose and disperse it by ultrasonication in an ultrasonicator. Then stir and adsorb it at 30°C for 12 h. Then add 80 g of sodium borohydride and 500 mL of water and stir to carry out reduction reaction at 20°C for 6 h. Filter and wash with deionized water. Then add it to 200 mL of deionized water and disperse it by ultrasonication. Finally, pre-freeze it at -35°C for 6 h. Then freeze-dry it at -60°C in a freeze dryer for 36 h to obtain heat dissipation aerogel.
[0031] Example 3
[0032] (1) Add 800 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene, 165 mmol of 3-amino-5-bromobenzoic acid, 5 mmol of palladium acetate, 520 mmol of sodium carbonate, and 120 mL of deionized water to a reaction vessel equipped with a condenser reflux tube, introduce nitrogen, heat to 85° C., stir to react for 10 h, add deionized water, place the reaction vessel in an ice water bath to precipitate a precipitate, filter, wash with deionized water, and then recrystallize with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene.
[0033] (2) Add 800 mL of N,N-dimethylformamide and 20 g of dialdehyde cellulose to a reaction container, stir and mix, then add 30 g of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, stir and react at 60° C. for 18 h, place the reaction container in an ice water bath, precipitate, filter, wash with ethanol, and dry to cross-link the carboxylated cellulose.
[0034] (3) Add 7 g of copper sulfate to 120 mL of deionized water and stir to dissolve, then add 3 g of cross-linked carboxylated cellulose and disperse it by ultrasonication in an ultrasonicator, then stir and adsorb it at 40°C for 6 h, then add 120 g of sodium borohydride and 800 mL of water and stir to perform reduction reaction at 20°C for 36 h, filter, wash with deionized water, then add to 200 mL of deionized water and disperse it by ultrasonication, finally pre-freeze at -25°C for 10 h, then freeze-dry in a freeze dryer at -60°C for 36 h to obtain heat dissipation aerogel.
[0035] Example 4
[0036] (1) Add 700 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene, 160 mmol of 3-amino-5-bromobenzoic acid, 4 mmol of palladium acetate, 450 mmol of sodium carbonate, and 100 mL of deionized water to a reaction vessel equipped with a condenser reflux tube, introduce nitrogen, heat to 90° C., stir to react for 8 h, add deionized water, place the reaction vessel in an ice water bath to precipitate a precipitate, filter, wash with deionized water, and then recrystallize with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene.
[0037] (2) Add 800 mL of N,N-dimethylformamide and 20 g of dialdehyde cellulose to a reaction container, stir and mix, then add 36 g of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, stir and react at 45° C. for 36 hours, place the reaction container in an ice water bath, precipitate, filter, wash with ethanol, and dry to cross-link the carboxylated cellulose.
[0038] (3) Add 9 g of copper nitrate to 150 mL of deionized water and stir to dissolve. Then add 3 g of cross-linked carboxylated cellulose and disperse it by ultrasonication in an ultrasonicator. Then stir and adsorb it at 30°C for 12 h. Then add 140 g of sodium borohydride and 1 L of water and stir to perform reduction reaction at 30°C for 24 h. Filter and wash with deionized water. Then add it to 200 mL of deionized water and disperse it by ultrasonication. Finally, precool it at -30°C for 8 h and freeze dry it at -50°C in a freeze dryer for 48 h to obtain heat dissipation aerogel.
[0039] Comparative Example 1
[0040] (3) 3 g of dialdehyde cellulose was added to 200 mL of deionized water, dispersed by ultrasound, and finally pre-frozen at -25°C for 10 h, and then freeze-dried in a freeze dryer at -50°C for 48 h to obtain heat dissipation aerogel.
[0041] Comparative Example 2
[0042] (1) Add 800 mL of N,N-dimethylformamide, 50 mmol of 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene, 165 mmol of 3-amino-5-bromobenzoic acid, 5 mmol of palladium acetate, 450 mmol of sodium carbonate, and 100 mL of deionized water to a reaction vessel equipped with a condenser reflux tube, introduce nitrogen, heat to 100° C., stir to react for 5 h, add deionized water, place the reaction vessel in an ice water bath to precipitate, filter, wash with deionized water, and then recrystallize with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene.
[0043] (2) Add 500 mL of N,N-dimethylformamide and 20 g of dialdehyde cellulose to a reaction container, stir and mix, then add 20 g of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, stir and react at 45° C. for 36 hours, place the reaction container in an ice water bath, precipitate, filter, wash with ethanol, and dry to cross-link the carboxylated cellulose.
[0044] (3) 3 g of cross-linked carboxylated cellulose was added to 200 mL of deionized water, dispersed by ultrasound, and finally pre-frozen at -25°C for 10 h, and then freeze-dried in a freeze dryer at -50°C for 48 h to obtain heat dissipation aerogel.
[0045] Comparative Example 3
[0046] Add 2.4g of copper chloride to 100mL of deionized water, stir to dissolve, then add 3g of dialdehyde cellulose, disperse by ultrasound in an ultrasonic instrument, then stir and adsorb at 20°C for 18h, then add 52g of sodium borohydride and 300mL of water, stir at 25°C for reduction reaction for 24h, filter, wash with deionized water, then add to 200mL of deionized water, disperse by ultrasound, finally pre-freeze at -25°C for 10h, then freeze-dry in a freeze dryer at -50°C for 48h to obtain heat dissipation aerogel.
[0047] Comparative Example 4
[0048] (1) Add 500 mL of N,N-dimethylformamide and 20 g of dialdehyde cellulose to a reaction container, stir and mix, then add 20 g of 1,3,5-tri(4-aminophenyl)benzene, stir and react at 45° C. for 36 hours, place the reaction container in an ice water bath, precipitate, filter, wash with ethanol, and dry to cross-link the cellulose.
[0049] (2) Add 2.4 g of copper chloride to 100 mL of deionized water and stir to dissolve. Then add 3 g of cross-linked cellulose and disperse it by ultrasonication in an ultrasonicator. Then stir and adsorb it at 20°C for 18 h. Then add 52 g of sodium borohydride and 300 mL of water and stir to carry out reduction reaction at 25°C for 24 h. Filter and wash with deionized water. Then add it to 200 mL of deionized water and disperse it by ultrasonication. Finally, pre-freeze it at -25°C for 10 h. Then freeze-dry it in a freeze dryer at -50°C for 48 h to obtain heat dissipation aerogel.
[0050] Referring to ISO 22007-2:2008, Part 2: Instantaneous Planar Heat Source (Heating Plate) Method, a thermal conductivity tester was used to test the thermal conductivity of the heat dissipating aerogel. The specifications of the aerogel were 30 cm × 30 cm × 10 cm.
[0051] The compression performance of the heat dissipation aerogel was tested using a microcomputer-controlled electronic universal testing machine, with a compression speed of 5 mm / min and a compression height of 70% of the original height. Five groups of samples were tested and the average value was taken.
[0052] The test results are shown in Table 1.
[0053] Table 1 Thermal conductivity and compression properties of heat dissipation aerogel
[0054]
[0055]
[0056] After testing, comparative example 1 uses dialdehyde cellulose as the matrix of aerogel, and its compressive stress (strain 70%) is 8.8 kPa, and its compression modulus is 82.4 kPa. The thermal conductivity is 0.039 W·m -1 ·k -1 , poor compression performance, poor thermal conductivity and heat dissipation performance.
[0057] In Examples 1 to 4, 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene containing multiple amino groups is used to undergo a Schiff base condensation reaction with the aldehyde group of dialdehyde cellulose to achieve cross-linking of dialdehyde cellulose to obtain cross-linked carboxylated cellulose containing carboxyl groups. The introduced carboxyl groups are then used to react with copper salts such as copper chloride to form Cu 2+ It has a strong coordination chelation effect and can 2+ Uniformly adsorbed into the skeleton and pores of cross-linked cellulose, and then reduced by sodium borohydride, Cu 2+ Nano copper particles are generated and evenly distributed in the skeleton of cross-linked cellulose. Finally, after freeze drying, heat dissipation aerogel is obtained. Nano copper particles are well dispersed in the aerogel and are not easy to agglomerate. They form heat conduction paths in the aerogel, significantly improving the thermal conductivity of the aerogel and showing better thermal conductivity and heat dissipation performance. After the dialdehyde cellulose is cross-linked with 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, a rigid terphenylbenzene structure is introduced into the skeleton of the aerogel ( ), significantly improving the strength and modulus of cellulose aerogel. At the same time, the nano-copper particles themselves have high mechanical strength and are embedded in the aerogel matrix, which can play the role of supporting the skeleton, making the aerogel show higher compressive stress, compression modulus and mechanical properties.
[0058] Compared with Example 1, Comparative Example 2 does not add copper salt, the aerogel does not contain copper nanoparticles, the thermal conductivity is very low, the thermal conductivity and heat dissipation performance are very poor, and the compressive stress and modulus are also lower than those of Example 1. However, the aerogel of Comparative Example 2 contains a rigid terphenyl benzene structure, and the compressive stress and modulus are significantly higher than those of Comparative Example 1.
[0059] The dialdehyde cellulose of Comparative Example 3 does not contain carboxyl groups. 2+ The coordination chelation and adsorption performance of Cu 2+ The Cu 2+ The generated nano copper particles are not evenly distributed in the skeleton of the cross-linked cellulose. The nano copper particles have poor dispersion in the aerogel and are easily agglomerated. A good heat conduction path is not formed, resulting in a thermal conductivity significantly lower than that of Example 1.
[0060] Comparative Example 4: 1,3,5-tri(4-aminophenyl)benzene was used as a crosslinking agent to react with dialdehyde cellulose. The obtained cellulose aerogel also contained a rigid triphenylbenzene structure, and the compressive stress and compression modulus were significantly improved. However, the obtained crosslinked cellulose did not contain carboxyl groups, and the Cu 2+ The coordination chelation and adsorption performance are poor, resulting in poor dispersion of the generated nano-copper particles in the aerogel, easy agglomeration, and no good heat conduction path is formed. The thermal conductivity is significantly lower than that of Example 1, and the compression performance is also lower than that of Example 1.
[0061] The above embodiments are only used to illustrate the present invention, but not to limit the present invention. Although the present invention is described in detail with reference to the embodiments, it should be understood by those skilled in the art that various combinations, modifications or equivalent substitutions of the technical solutions of the present invention do not depart from the spirit and scope of the technical solutions of the present invention, and should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a heat dissipation aerogel, characterized in that: The preparation method is: (1) Add N,N-dimethylformamide and dialdehyde cellulose to a reaction container, stir and mix, then add 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene, stir and react, then place the reaction container in an ice water bath to precipitate, filter, wash with ethanol, and dry to cross-link the carboxylated cellulose; (2) adding copper salt to deionized water, stirring to dissolve, then adding cross-linked carboxylated cellulose, ultrasonically dispersing in an ultrasonic instrument, then stirring to adsorb, then adding sodium borohydride and water, stirring to carry out a reduction reaction, filtering, washing with deionized water, then adding to deionized water, ultrasonically dispersing, and finally pre-freezing and freeze-drying to obtain heat dissipation aerogel.
2. The method for preparing the heat dissipation aerogel according to claim 1, characterized in that: The mass of the 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene is 50-180% of the mass of the dialdehyde cellulose.
3. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The reaction in (1) is carried out at 45-60°C for 18-36 hours.
4. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The mass of the copper salt is 80-300% of the mass of the cross-linked carboxylated cellulose.
5. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The copper salt is copper chloride, copper sulfate or copper nitrate.
6. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The stirring adsorption in (2) is carried out at 20-40°C for 6-18 hours.
7. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The reduction reaction in (2) is carried out at 20-30°C for 24-36 hours.
8. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The pre-freezing in (2) is carried out at -25°C to -35°C for 6-10 hours; and freeze-drying is carried out at -50°C to -60°C for 36-48 hours.
9. The method for preparing heat dissipation aerogel according to claim 1, characterized in that: The preparation method of 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene comprises: adding N,N-dimethylformamide, 1,3,5-tris[4-(dihydroxyboryl)phenyl]benzene in a ratio of 1 mol:(3-3.3) mol:(0.08-0.1) mol:(9-10.8) mol, 3-amino-5-bromobenzoic acid, palladium acetate, sodium carbonate into a reaction container provided with a condenser reflux tube, adding deionized water, introducing nitrogen, heating to 85-100° C., stirring for reaction for 5-10 hours, adding deionized water, placing the reaction container in an ice water bath to precipitate a precipitate, filtering, washing with deionized water, and then recrystallizing with ethanol to obtain 1,3,5-tris[4-(3-aminobenzoic acid)phenyl]benzene.
10. Use of the heat dissipation aerogel obtained by the preparation method according to any one of claims 1 to 9 in lithium batteries.
Citation Information
Patent Citations
Cellulose supported nano-copper (I) porous material, and preparation method and application thereof
CN107715911A
Water-absorbing aerogel pad prepared from in-situ synthesized nano-silver and application of water-absorbing aerogel pad to fresh keeping of chilled beef
CN113207947A
Hierarchical pore structure composite aerogel and preparation method thereof
CN114316375A
Nano cellulose aerogel and preparation method thereof
CN115260570A
Preparation process of high-strength polyurethane thermal insulation material
CN118240173A